2013
DOI: 10.1590/s1413-81232013001200007
|View full text |Cite
|
Sign up to set email alerts
|

Fatores socioambientais associados à ocorrência de quedas em idosos

Abstract: Fatores socioambientais associados à ocorrência de quedas em idososSocial and environmental factors associated with the occurrence of falls in the elderly

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
42

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(53 citation statements)
references
References 17 publications
0
11
0
42
Order By: Relevance
“…Ao analisar a queda nos idosos com 80 anos ou mais de idade, Aguiar & Assis 26 e Pereira et al 27 encontraram, respectivamente, 29,6% e 20,8%. Possivelmente, fatores como maior oscilação da marcha, fragilidade e incapacidade funcional, bem como maior número de doenças crônicas, podem estar envolvidos com a ocorrência de quedas em idades avançadas.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Ao analisar a queda nos idosos com 80 anos ou mais de idade, Aguiar & Assis 26 e Pereira et al 27 encontraram, respectivamente, 29,6% e 20,8%. Possivelmente, fatores como maior oscilação da marcha, fragilidade e incapacidade funcional, bem como maior número de doenças crônicas, podem estar envolvidos com a ocorrência de quedas em idades avançadas.…”
Section: Discussionunclassified
“…No estudo de Paula et al, 1 a maioria dos idosos internada por queda possui escolaridade até o primário incompleto. Pereira et al 27 afirmam que idosos com mais anos de estudo possuem menor risco para quedas, fato que pode estar relacionado a maior renda em idosos com maior escolaridade, e consequentemente, melhores condições de moradia e acesso à saúde, o que não foi comprovado no presente estudo para óbitos por queda.…”
Section: Discussionunclassified
“…O estudo realizado por Pereira et al (2013) teve como objetivo avaliar os fatores socioambientais quando relacionados a quedas. Os autores utilizaram como amostra uma população de 6.715 idosos de 59 cidades.…”
Section: Resultsunclassified
“…In terms of the clinical and medication related characteristics and the environmental risk factors related to the hospitalization of elderly patients who suffered falls, studies indicate that the main risk factors for falls in this population are related to functional limitation 31,32 , a previous history of falls, increased age 33 , muscle weakness 34 , use of psychotropic medications 29 , environmental risks, the female gender 4,8,15,18,19,21 , as well as visual impairment. Although the present study identified a greater occurrence of hospitalization due to falls in patients with renal disease, no studies were found in literature to verify this association.…”
Section: Discussionmentioning
confidence: 99%